2021
DOI: 10.3390/medicina57101050
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Gene for ABCC2 Transporter Predicts Methotrexate Drug Survival in Patients with Psoriasis

Abstract: Background and Objectives: Methotrexate is widely prescribed for the treatment of moderate-to-severe psoriasis. As drug survival encompasses efficacy, safety, and treatment satisfaction, such studies provide insights into successful drug treatments in the real-life scenario. The objective was to define methotrexate drug survival and reasons for discontinuation, along with factors associated with drug survival, in a cohort of adult patients with moderate-to-severe plaque psoriasis. Materials and Methods: Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…24,25 An interesting approach is adopted by Grželj et al who showed a possible association between MTX efficacy and ABCC2 polymorphism (rs717620) in patients diagnosed with psoriasis who received low-dose MTX therapy. 26 In this study, the authors demonstrated that MTX drug survival has been significantly longer in patients carrying a T allele in ABCC2 (rs717620, C > T) than patients carrying ABCC2 (rs717620, C > T) CC genotype who discontinued their treatment due to a lack of treatment response (hazard ratio, 0.606; 95% confidence interval, 0.380-0.967; p = 0.036). However, in paediatric oncology it is common to administrate high-dose (HD) MTX (dose >500 mg/m 2 ) that could potentially lead to prolonged MTX exposure in paediatric patients carrying an ABCC2 (rs717620, C > T) variant.…”
Section: Methotrexate-induced Toxicitymentioning
confidence: 71%
“…24,25 An interesting approach is adopted by Grželj et al who showed a possible association between MTX efficacy and ABCC2 polymorphism (rs717620) in patients diagnosed with psoriasis who received low-dose MTX therapy. 26 In this study, the authors demonstrated that MTX drug survival has been significantly longer in patients carrying a T allele in ABCC2 (rs717620, C > T) than patients carrying ABCC2 (rs717620, C > T) CC genotype who discontinued their treatment due to a lack of treatment response (hazard ratio, 0.606; 95% confidence interval, 0.380-0.967; p = 0.036). However, in paediatric oncology it is common to administrate high-dose (HD) MTX (dose >500 mg/m 2 ) that could potentially lead to prolonged MTX exposure in paediatric patients carrying an ABCC2 (rs717620, C > T) variant.…”
Section: Methotrexate-induced Toxicitymentioning
confidence: 71%
“… 26 A study analyzing the drug survival of MTX in 117 patients showed ABCC2 rs717620 genotype was significantly associated with drug survival, with variant T allele associated with longer drug survival. 27 Fan et al performed a study to assess if polymorphisms of the annexin A6 (ANxA6) gene, that confers psoriasis susceptibility, were associated with response to MTX. 28 They found out that the rs11960458 polymorphism was statistically significantly associated with response to MTX both in the short (12 weeks) and long-term (1 year).…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors for the development of graft survival with the presence of acute graft rejection and/or ATN included the genetic polymorphisms studied, demographic characteristics such as age, baseline BMI and underlying comorbidities as well as transplantrelated factors and ADR due to immunosuppressive regimen (Table 3). Genetic factors were included to determine their effects on the model as well as all variables that demonstrated a p-value of <0.25 [27]. Following a multiple logistic analysis, the wildtype ABCC2 -24C>T C allele (adjusted Odd Ratios [aOR]: 27.675, 95% confidence interval [CI]: 1.204, 636.151), presence of DGF (aOR: 49.214, 95% CI: 2.366, 1023.731) and CMV infection (aOR: 18.097, 95% CI: 2.036, 160.867) resulted in an increased risk of graft survival with complications (Table 3).…”
Section: Factors Associated With Graft Survival In the Presence Of Ac...mentioning
confidence: 99%